2020
DOI: 10.1152/ajprenal.00272.2019
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid and inflammation in kidney disease

Abstract: Asymptomatic hyperuricemia is frequently observed in patients with kidney disease. Although a substantial number of epidemiologic studies have suggested that an elevated uric acid level plays a causative role in the development and progression of kidney disease, whether hyperuricemia is simply a result of decreased renal excretion of uric acid or is a contributor to kidney disease remains a matter of debate. Over the last two decades, multiple experimental studies have expanded the knowledge of the biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 158 publications
0
56
0
Order By: Relevance
“…The major symptom of a gout flare is the MSU crystal-induced sterile inflammation with UA controversially being an intrinsic inhibitor of MSU crystal-induced tissue inflammation [49] and a direct promoter in inflammation in vivo [50]. Hyperuricemia could induce an activated status of inflammation [51] or autoinflammation [52].…”
Section: Distinct Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%
See 1 more Smart Citation
“…The major symptom of a gout flare is the MSU crystal-induced sterile inflammation with UA controversially being an intrinsic inhibitor of MSU crystal-induced tissue inflammation [49] and a direct promoter in inflammation in vivo [50]. Hyperuricemia could induce an activated status of inflammation [51] or autoinflammation [52].…”
Section: Distinct Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%
“…Moreover, asymptomatic hyperuricemia patients usually display less potency of inflammation with a lower number of NKG2D + (activating receptors of simulation of cytotoxicity) NK cells [63]. It could be speculated that under hyperuricemia condition the UA paradox interrelationship of the contradictory dual effects of inflammation [49,50] results from SUA "neutralizing" the inflammation produced oxygen species to protect tissue damages. It has also been discovered that some lipids from diet or alcohol consumption could directly trigger gout flares by activation of NALP-3 inflammasome through binding to toll-like receptors [64] or alteration of glucose and apolipoprotein metabolism [65], respectively.…”
Section: Distinct Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%
“…In the last 20 years, several clinical studies demonstrated as serum UA is a concomitant of high-risk conditions and a predictor of unfavorable outcomes. As a matter of fact, association of hyperuricemia with metabolic syndrome, kidney function impairment, and its impact on cardiovascular disease and mortality is well established [4,[6][7][8][9][10]140] . By a pathophysiological point of view, these data are consistent with the hypothesis that UA induces and perpetuates reno-vascular injury, leading to a progressive vicious cycle of further renal damage and thereafter to an increased cardiovascular and all-cause mortality risk.…”
Section: Endothelial Cell/smooth Muscle Cell Interactionsmentioning
confidence: 99%
“…The major symptom of a gout attack or flare is the MSU crystal-induced sterile inflammation with UA controversially being an intrinsic inhibitor of MSU crystal-induced tissue inflammation [49] and a direct promoter in inflammation in vivo [50]. Hyperuricemia could induce an activated status of inflammation [51] or autoinflammation [52].…”
Section: Deferent Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%
“…Moreover, asymptomatic hyperuricemia patients usually display less potency of inflammation with a lower number of NKG2D + (activating receptors of simulation of cytotoxicity) NK cells [63]. It could be speculated that under hyperuricemia condition the UA paradox inter-relationship of the contradictory dual-effects to inflammation [49,50] is resulted from SUA to "neutralize" the inflammation produced oxygen species to protect tissue damages. It has also been discovered that some lipids from diet or alcohol consumption could directly trigger gout flare by activation of NALP-3 inflammasome through binding to toll-like receptors [64] or alteration of glucose and apolipoprotein metabolism [65], respectively.…”
Section: Deferent Reaction and Priming Pathways Of Inflammation By Sumentioning
confidence: 99%